Postgraduate's Dermatology E-logbook - Perceptions of Faculty and Residents: A Survey - Shankar Bharathi Ashwini; Garehatty Rudrappa Kanthraj; Shastry Veeranna; Basavana Gowdappa Hatthur (Wolters Kluwer Medknow Publications, 2024)
Background: Medical postgraduation is a learning/training period during which residents will be assessed based on their academic performances. Various tools are available to assess postgraduate's academic work, one important tool being a logbook. Dermatology is a visual specialty, and there are advances in information technology and teledermatology. E-logbook assumes its significance in dermatology. Recently, E-logbook is used in various specialties in other countries. E-logbook has not been used in India in dermatology or other specialties. In India, E-logbook has remained only as a concept in medical education. Aims: A survey was performed to obtain the views/perceptions/suggestions of students and faculty for E-logbook in dermatology. Methods: We used a questionnaire for students and faculty of the dermatology department at a tertiary care hospital. The questionnaire which is based on the fundamentals that form the triad of E-logbook includes (a) principles, (b) benefits for students, and (c) faculty. The survey had 26 questions to be answered by faculty and the first 17 to be answered by students. Both students and faculty were asked to provide their reasons with respect to their views. Statistical analysis was performed. Results: Majority of the respondents agreed with P (0.001) for principles, benefits for students, and faculty. Limitations: The study was confined to students and faculty of a single dermatology department. Conclusions: Faculty and students favor E-dermatology logbook. Interesting cases and dermatosurgery/esthetic procedures can be stored, and faculty can assess and monitor the skills of postgraduates. We strongly recommend E-dermatology logbook app.